2017
DOI: 10.5539/jmsr.v6n4p19
|View full text |Cite
|
Sign up to set email alerts
|

Specimen's Geometry Related Influences on Load-Bearing Capacity of Joining Aluminium and UHSS by Innovative Shear-Clinching

Abstract: Economic conditions as well as comfort and safety-related requirements lead to lightweight design especially in automotive body-in-white production processes. The consequential multi-material mix limits the reliability of conventional thermal joining technologies. Innovative mechanical joining technologies need to be established. Following the lightweight-design requirements, next step for weight-reduction would be the renunciation of additional elements. Clinching technologies support this idea by creating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A servo motor-driven clinching system ECKOLD DFG 500/150E with a feed speed of 40 mm/s was applied for joining. With regard to the shear-clinching system following [15], the punch-side tool set has an inner diameter di = 5.6 mm, the outer punch radius r = 6.0 mm. An opening die was positioned on the die side.…”
Section: /1mentioning
confidence: 99%
“…A servo motor-driven clinching system ECKOLD DFG 500/150E with a feed speed of 40 mm/s was applied for joining. With regard to the shear-clinching system following [15], the punch-side tool set has an inner diameter di = 5.6 mm, the outer punch radius r = 6.0 mm. An opening die was positioned on the die side.…”
Section: /1mentioning
confidence: 99%
“…In [10], it was shown that the maximum joining force differed by 7% when joining single lap shear tensile and cross tensile specimens due to the changed edge distances. The shear-clinching joint has a smaller edge distance of 8 mm in the single lap shear tensile specimen, so more aluminium is pressed out of the joining zone, which led to decreasing the volume of aluminium in the joining zone and reducing the joining force.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…For realising the shear-clinching joining, a c-shaped stand machine with a maximum load of 150 kN is used, which shows a high-rigidity until a load approaches 65 kN. The experimental setup of the tool follows the condition in [10]. In the investigations, only the joints are produced, which are classified as a good shear-clinched joint in [11].…”
mentioning
confidence: 99%
“…Therefore, new and innovative joining techniques are required for joining such combination of steel and aluminum sheets in general [5]. The main problem of joining steel and aluminum sheets is in their different level of the melting temperatures and the presence of the surface oxide layer high heat conductivity (in the case of aluminum) hence they are difficult to weld.…”
Section: Introductionmentioning
confidence: 99%